English mead, Polish miód and German Met from a historical and comparative perspective - Rychło, Mikołaj (Acta Universitatis Lodziensis. Folia Germanica, 2018)
The paper presents a diachronic analysis of Polish miód ‘honey’, English mead and German Met ‘mead’ conducted according to a new approach to contrastive studies.Taking into account potential cognates in other languages, the work aims to investigate the evolution of the common ancestor word *medh-u- in two lines of development: the Slavic leading to modern Polish, and the Germanic leading to modern English and High German. In order to understand these branching paths, the pertinent sound changes have been identified, which transformed the common proto-form. These developments are illustrated with further examples and, in the summary, ordered chronologically. The paper also discusses an old compound *medvědь (Polish niedźwiedź), which can be considered a taboo designation for a bear, and contains also the root *medъ ‘honey’.